Analysis of Students' Mathematical Critical Thinking Skills and Collaborative Collaboration Skills - Retno Ayu Trisnawati; Ali Mahmudi (PT Publikasiku Academic Solution, 2023)
This study will provide an overview of the relationship between student collaboration and the mathematical critical thinking skills of grade VIII-F students of SMP N 1 Yogyakarta. The correlational technique is a technique used to test the relationship between the two variables. Based on the findings, there is a linear relationship between the mathematical critical thinking capacity of learners and the willingness to work together. The conclusion that can be drawn is that there is a substantial relationship between collaboration skills and mathematical critical thinking skills of grade VIII-F students of SMP N 1 Yogyakarta because of r_hitung>r_tabel (0.467>0.29). so that the conclusion that can be obtained is that there is a significant relationship between the ability to think critically mathematically and the collaboration of students of VIII-F SMP N 1 Yogyakarta. In addition, the relationship between the two research variables was positive because r_hitung= 0.467. Overall, students' collaboration skills fall into the medium, high, and very high categories, while their mathematical critical thinking skills fall into the low, medium, and high categories. However, some of them have collaboration skills that fall into the medium category but have low mathematical critical thinking skills, and there are also students who have collaboration skills that fall into the high category but have medium mathematical critical thinking skills. Low mathematical critical thinking skills make students unable to express reasons and justifications accurately. Although learners with intermediate critical thinking skills can provide reasonable justifications for such questions, the arguments they provide may not be entirely valid.